2002
DOI: 10.1108/09544780210429852
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the difficulties of implementing quality management in Yemen

Abstract: Total quality management (TQM) is still a new issue for the organisations in Yemen. These organisations need to establish a new strategy towards quality management. Focuses on the difficulties and barriers to the introduction and implementation of TQM in such a culture. The researcher draws on two case study organisations and on the activities proposed by the European excellence model to exemplify TQM. Time was spent explaining these activities to the people involved and was followed by a discussion of the dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 10 publications
2
32
0
Order By: Relevance
“…The study concluded a lack of technical knowledge in organizations to implement a quality management system (QMS). In another study by Al-Zamany et al (2002b), the authors surveyed attitudes toward TQM in Yemen. A survey of 18 companies was undertaken to understand the issues in implementing the TQM principle.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study concluded a lack of technical knowledge in organizations to implement a quality management system (QMS). In another study by Al-Zamany et al (2002b), the authors surveyed attitudes toward TQM in Yemen. A survey of 18 companies was undertaken to understand the issues in implementing the TQM principle.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, many researchers have revealed that the major problem of quality management implementation is the lack of top management commitment and participation which leads to its eventual failure [21,22,23,24].…”
Section: ) Top Management Commitmentmentioning
confidence: 99%
“…Ineffective communication delays the process of organisational change and leads to conflicts and damaged relationships between people (Paper et al, 2001). Effective communication is important for the success of change programmes (Al-Zamany et al, 2002;McGreevy, 2009;Paper et al, 2001). It affects organisational culture and contributes to the overall effectiveness of the change programme (Nordvang et al, 2008).…”
Section: Problem-solving Mindsetmentioning
confidence: 99%